Implementasi Kebijakan Value Added Tax Refund (Pengembalian PPN) bagi Perwakilan Diplomatik antara Negara Swedia dan Indonesia - Dewi, Riani; Rosdiana, Haula (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
Tax policy in every country has difference outcome in implementation. The difference of policy in VAT (Value Added Tax) Refund process and other country, especially for Diplomatic Representatives is determined by the principle of reciprocity. The purpose of this study is to analyze policy of VAT Refund regulations between diplomatic representative for Sweden and Indonesia, also the adversity in the policy implementation. The analysis of tax refund process will be focused on the authority, tax objects, tax subjects, tax return processes. This type of research uses a qualitative method with a descriptive approach scope to analyze theimplementation of VAT refund in Indonesia to all diplomatic representative. The Findings are the absence of a policy that regulates the time period for the process of tax returns for Diplomatic Representatives and the absence of an integrated online system between the Directorate General of Protocol and Consular, Diplomatic Representatives and Foreign Corporate & Individual (Badora) Tax Service Office to facilitate and reduce human errors.